JUNIO a cooking pot carrier for the transportation of food in feeding programs - Tuazon, Edmar Tacata (College of Fine Arts, University of the Philippines Diliman, 2017)
Hunger has already been an underlying issue of the Philippines, particularly to children. To give assistance to their need, various organizations are conducting feeding programs. However, as the hot meals prepared are being transported to the feeding area, inconveniences such as heaviness, food spill and heat contact from the cooking pot surface are evident. These issues can affect the whole transport system of food in feeding programs. Considering these factors, this thesis will review and study the different factors regarding the food transport in outreach feeding programs. Mixing these considerations all together, JUNIO was designed to ensure a more efficient and secured transportation of food in feeding programs. As feeding programs try to reach more children, the design will give assistance to carrying of food that will give warmth to the starving stomachs of those who are involuntary hungry.